Method for improving electrochemical performance of battery and electrochemical device

By using an external magnetic field to optimize the magnetic structure of the positive electrode sheet in lithium-ion batteries, the problem that lithium-ion batteries are difficult to take into account high-rate performance when increasing the energy density, and the overall performance improvement of the battery is achieved.

CN119890460APending Publication Date: 2025-04-25EVE POWER CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411837057.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

While increasing the energy density, existing lithium-ion batteries are difficult to have high-rate performance. Thick electrodes lead to poor electrode wetting and hindering charge transport.

Method used

By placing the battery in an applied magnetic field, the magnetic field direction intersects with the plane of the positive electrode sheet, changing the magnetic structure of the material in the positive electrode sheet, and building a crystal surface that is conducive to the embedding and disengagement of lithium ions.

Benefits of technology

It improves the energy density and rate performance of the battery, enhances the electrochemical reaction efficiency, and extends the cycle life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005187781510000121
    Figure BDA0005187781510000121
  • Figure BDA0005187781510000131
    Figure BDA0005187781510000131
Patent Text Reader

Abstract

The invention provides a method for improving the electrochemical performance of a battery and an electrochemical device, and relates to the technical field of batteries, the method for improving the electrochemical performance of the battery comprises the following steps: placing the battery in an external magnetic field; the battery comprises a positive plate with the surface density of 220g / m < 2 >-300g / m < 2 >, and the thickness of the positive plate is greater than 400mu m; the positive plate comprises graphene; an applied magnetic field is configured to penetrate the positive plate. According to the method for improving the electrochemical performance of the battery, the energy density and the rate capability of the battery can be improved at the same time, and the comprehensive performance of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a method and an electrochemical device for improving the electrochemical performance of a battery. Background Art

[0002] With the continuous growth of the electric vehicle market and the energy storage field, higher and higher requirements are placed on the energy density and rate performance of lithium-ion batteries. In the related technology, in order to improve the energy density of lithium-ion batteries, methods such as increasing the electrode compaction density and thickness are usually adopted. However, thick electrodes easily lead to poor electrode wettability and obstructed charge transport, which leads to a decrease in the rate performance of the battery. In addition, although increasing the porosity of the electrode material can effectively improve the rate performance of lithium-ion batteries, it will affect the energy density. Therefore, how to make lithium-ion batteries have both high energy density and high rate performance is still a big challenge. Summary of the invention

[0003] The embodiments of the present application provide a method and an electrochemical device for improving the electrochemical performance of a battery, which can simultaneously improve the energy density and rate performance of the battery and enhance the overall performance of the lithium-ion battery.

[0004] In a first aspect, an embodiment of the present application provides a method for improving the electrochemical performance of a battery, comprising:

[0005] placing the battery in an applied magnetic field;

[0006] Among them, the battery includes a surface density of 220g / m 2 -300g / m 2 A positive electrode sheet having a thickness greater than 400 μm; a material of the positive electrode sheet includes graphene; and a magnetic field direction of the external magnetic field intersects with a plane where the positive electrode sheet is located.

[0007] In some embodiments, the magnetic field strength of the external magnetic field is 0.5T-1T.

[0008] In some embodiments, before placing the battery in an external magnetic field, the method further comprises:

[0009] Applying the positive electrode composite material to at least one side of the current collector to form a positive electrode sheet; wherein the positive electrode composite material includes graphene;

[0010] The positive electrode sheet, the negative electrode sheet and the separator are assembled to form a battery.

[0011] In some embodiments, the positive electrode composite material includes a positive electrode active material, a conductive agent, graphene, and a binder;

[0012] Among them, the mass ratio of the positive electrode active material, the conductive agent, the graphene and the binder is (91-95):(2-4):(0.5-1.5):(2.5-3.5).

[0013] In some embodiments, the positive electrode active material includes at least one of lithium iron phosphate and lithium manganese iron phosphate.

[0014] In some embodiments, the conductive agent includes conductive carbon black.

[0015] In some embodiments, the binder includes polytetrafluoroethylene.

[0016] In some embodiments, applying the positive electrode composite material to at least one side of the current collector comprises:

[0017] The positive electrode active material, the conductive agent, the graphene and the binder are mixed in proportion to obtain a positive electrode composite material;

[0018] The positive electrode composite material is subjected to a first rolling process to obtain an electrode membrane;

[0019] The electrode film is attached to at least one side of the current collector and a second rolling process is performed to obtain a positive electrode sheet.

[0020] In some embodiments, the angle between the magnetic field direction of the external magnetic field and the plane where the positive electrode sheet is located is 60°-90°.

[0021] In a second aspect, an embodiment of the present application provides an electrochemical device, including a battery and a magnetic field assembly;

[0022] The battery includes a surface density of 220g / m 2 -300g / m 2 A positive electrode sheet having a thickness greater than 400 μm; the positive electrode sheet includes graphene;

[0023] The magnetic field assembly is configured to generate an external magnetic field, and the external magnetic field is configured to penetrate the positive electrode sheet.

[0024] Beneficial effects of the embodiments of the present application:

[0025] The method for improving the electrochemical performance of a battery provided in the embodiment of the present application has a battery surface density of 220 g / m 2 -300g / m 2The positive electrode sheet, and the thickness of the positive electrode sheet is greater than 400μm, that is, the positive electrode sheet of the battery is a thick electrode, so that the energy density of the battery is improved. Among them, the positive electrode sheet includes graphene, which has extremely high conductivity and two-dimensional planar structure, which helps to increase the transmission speed of electrons in the positive electrode sheet, reduce resistance, and thus improve the rate performance of the battery. In addition, the battery is placed in an external magnetic field, and the magnetic field direction of the external magnetic field intersects with the plane where the positive electrode sheet is located, so that the external magnetic field can penetrate the positive electrode sheet, change the magnetic structure of the material in the positive electrode sheet, and construct crystals that are more conducive to the embedding and extraction of lithium ions and crystal planes that are conducive to electrochemical reactions, thereby further improving the electrochemical performance of the battery. In other words, the method for improving the electrochemical performance of a battery provided in the present application can simultaneously improve the energy density and rate performance of the battery, and improve the overall performance of the battery. DETAILED DESCRIPTION

[0026] The technical solutions in the embodiments of the present application will be described clearly and completely below. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present application. In addition, it should be understood that the specific embodiments described herein are only used to illustrate and explain the present application, and are not used to limit the present application.

[0027] In a first aspect, an embodiment of the present application provides a method for improving the electrochemical performance of a battery, comprising:

[0028] The battery is placed in an applied magnetic field of magnetic field strength.

[0029] Among them, the battery includes a surface density of 220g / m 2 -300g / m 2 A positive electrode sheet having a thickness greater than 400 μm; a material of the positive electrode sheet includes graphene; and a magnetic field direction of the external magnetic field intersects with a plane where the positive electrode sheet is located.

[0030] In the method for improving the electrochemical performance of a battery provided in the embodiment of the present application, the battery includes a surface density of 220 g / m 2 -300g / m 2The positive electrode sheet, and the thickness of the positive electrode sheet is greater than 400μm, that is, the positive electrode sheet of the battery is a thick electrode, so that the energy density of the battery is improved. Among them, the positive electrode sheet includes graphene, which has extremely high conductivity and two-dimensional planar structure, which helps to increase the transmission speed of electrons in the positive electrode sheet, reduce resistance, and thus improve the rate performance of the battery. In addition, the battery is placed in an external magnetic field, and the magnetic field direction of the external magnetic field intersects with the plane where the positive electrode sheet is located, so that the external magnetic field can penetrate the positive electrode sheet, change the magnetic structure of the material in the positive electrode sheet, and construct crystals that are more conducive to the embedding and extraction of lithium ions and crystal planes that are conducive to electrochemical reactions, thereby further improving the electrochemical performance of the battery. In other words, the method for improving the electrochemical performance of a battery provided in the present application can simultaneously improve the energy density and rate performance of the battery, and improve the overall performance of the battery.

[0031] For example, the surface density of the positive electrode sheet can be 220 g / m 2 , 230g / m 2 , 240g / m 2 , 250g / m 2 , 260g / m 2 , 270g / m 2 , 280g / m 2 , 290g / m 2 or 300g / m 2 .

[0032] In some embodiments, the battery is a lithium-ion battery. As a widely used battery, lithium-ion batteries have the advantages of high energy density, high platform voltage, long cycle life, and wide operating temperature range. 2 -300g / m 2 The positive electrode sheet can significantly increase the load of positive electrode active materials and reduce the ratio of inactive components, thereby improving the energy density of the battery. However, when the surface density is high, the thickness of the positive electrode sheet will increase, which will increase the transmission distance of lithium ions in the positive electrode sheet, increase the stress and deformation generated by the diffusion reaction, increase the battery impedance, and reduce the battery rate performance and electrode reaction kinetics. The embodiment of the present application improves the above problems by applying an external magnetic field, so that the lithium-ion battery can reduce adverse reactions and improve the battery rate performance while increasing the battery energy density through the positive electrode sheet with a larger surface density.

[0033] In some embodiments, the magnetic field strength of the external magnetic field is 0.5T-1T. High magnetic field strength can easily cause more heat to be generated inside the battery, especially during the electrochemical reaction. If the heat cannot be dissipated in time, it may cause the battery temperature to rise, thereby affecting the performance and safety of the battery. In addition, complex equipment and a large amount of energy are required to generate and maintain high magnetic field strength. If the magnetic field strength is too low, the effect of improving the electrochemical performance of the battery is not obvious. The embodiment of the present application sets the magnetic field strength to 0.5T-1T, which can ensure the effect of improving the electrochemical performance of the battery, while reducing the problem of excessive battery temperature caused by excessive magnetic field strength and reducing costs.

[0034] Illustratively, the magnetic field strength of the external magnetic field may be 0.5T, 0.6T, 0.7T, 0.75T, 0.8T, 0.9T or 1T.

[0035] In some embodiments, before placing the battery in an external magnetic field, the method further comprises:

[0036] Applying the positive electrode composite material to at least one side of the current collector to form a positive electrode sheet; wherein the positive electrode composite material includes graphene;

[0037] The positive electrode sheet, the negative electrode sheet and the separator are assembled to form a battery.

[0038] The current collector can serve as a carrier for the positive electrode composite material. The current collector has good conductivity and can ensure rapid transmission of electrons within the battery, thereby improving the battery's charge and discharge efficiency. Applying the positive electrode composite material to at least one side of the current collector to combine the two helps to improve the structural stability of the positive electrode sheet and reduce deformation caused by material expansion or contraction during charge and discharge.

[0039] For example, aluminum foil can be selected as the current collector. Aluminum foil has high conductivity and can quickly transfer charge and heat energy, which helps to ensure the efficiency and reliability of the battery. The surface of aluminum foil is flat and not easy to bend. It can withstand the high pressure and high temperature during battery operation. At the same time, it is not easy to deform and break, ensuring the stability and safety of the battery. Compared with other materials, aluminum foil is more stable at the high potential of the positive electrode and is not easily oxidized. This is because aluminum will form a dense aluminum oxide protective film in the air, which effectively prevents the electrolyte from corroding the aluminum foil and improves the electrochemical reaction efficiency of the battery.

[0040] After the positive electrode sheet is formed, the positive electrode sheet is assembled with the negative electrode sheet and the separator to form a battery. The types and materials of the negative electrode sheet and the separator are not limited in the embodiments of the present application, and those skilled in the art can make reasonable choices according to actual needs.

[0041] In some embodiments, the positive electrode composite material includes a positive electrode active material, a conductive agent, graphene and a binder. Wherein, the mass ratio of the positive electrode active material, the conductive agent, the graphene and the binder is (91-95): (2-4): (0.5-1.5): (2.5-3.5). By increasing the proportion of the positive electrode active material in the positive electrode composite material, the loading rate of the positive electrode active material in the positive electrode sheet can be increased, and the energy density of the battery can be effectively improved.

[0042] Illustratively, the mass ratio of the positive electrode active material, the conductive agent, the graphene, and the binder may be 93:3:1:3.

[0043] In some embodiments, the positive electrode active material includes at least one of lithium iron phosphate and lithium iron manganese phosphate. Lithium iron phosphate has high temperature stability, can show high stability under high temperature conditions, is not prone to thermal runaway or combustion, thereby improving the safety of the battery. Lithium iron phosphate has a high theoretical specific capacity and can increase the energy density of the battery as a positive electrode active material. Lithium iron manganese phosphate has a high energy density and excellent stability, so that the battery can store more electrical energy and has better reliability.

[0044] It is understandable that the positive electrode active materials in the embodiments of the present application include lithium iron phosphate and lithium iron manganese phosphate for exemplary purposes only, and those skilled in the art may also select other positive electrode active materials, such as ternary lithium materials, according to actual needs.

[0045] In some embodiments, the conductive agent includes conductive carbon black. Conductive carbon black has excellent conductivity, can reduce the internal resistance of the positive electrode sheet, improve the electron transfer rate of the battery, and thus increase the output power and cycle life of the battery. In addition, conductive carbon black can also reduce the polarization phenomenon of the positive electrode composite material in the positive electrode sheet, and improve the safety performance and stability of the battery.

[0046] Furthermore, the conductive agent includes Super P. Super P is a small particle conductive carbon black with an extremely small particle size, which helps to form a dense conductive network in the positive electrode sheet, and has a large specific surface area, which increases the contact area with the positive electrode active material and can improve the conductive efficiency.

[0047] In some embodiments, the binder includes polytetrafluoroethylene. Polytetrafluoroethylene (PTFE) has good chemical stability, high temperature resistance, and good insulation performance. Using polytetrafluoroethylene as a binder can improve the high temperature resistance and corrosion resistance of the positive electrode sheet.

[0048] It is understandable that the binder in the positive electrode composite material may also be other binders such as polyvinylidene fluoride and polyvinyl alcohol.

[0049] In some embodiments, applying the positive electrode composite material to at least one side of the current collector comprises:

[0050] The positive electrode active material, the conductive agent, the graphene and the binder are mixed in proportion to obtain a positive electrode composite material;

[0051] The positive electrode composite material is subjected to a first rolling process to obtain an electrode membrane;

[0052] The electrode film is attached to at least one side of the current collector and a second rolling process is performed to obtain a positive electrode sheet.

[0053] Among them, in the process of mixing the positive electrode active material, the conductive agent, the graphene and the binder according to the proportion, mechanical stirring or ball milling can be used for mixing so that each component is fully dispersed to form a uniform positive electrode composite material.

[0054] The positive electrode composite material is subjected to the first rolling process to make the positive electrode composite material more compact, improve conductivity and structural strength, and form an electrode film with a certain thickness and strength through the first rolling process, which helps to control the thickness and uniformity of the positive electrode film. After the first rolling process, the thickness of the formed electrode film is about 500 μm.

[0055] After the electrode membrane is formed, the electrode membrane is further compounded with the current collector through a second rolling process to improve the bonding force between the electrode membrane and the current collector, reduce the problem of the electrode membrane falling off or stratification from the current collector surface during the battery charging and discharging process, and improve the overall strength and structural stability of the positive electrode sheet. + After the second rolling process, the electrode membrane and the current collector are combined into a whole, and the thickness of the electrode membrane can be further compressed to about 450μm.

[0056] It is understandable that the preparation method of the positive electrode sheet provided in the embodiments of the present application is only for illustrative purposes, and those skilled in the art may adopt other conventional methods in the art to prepare the positive electrode sheet, as long as the surface density of the positive electrode sheet and the selection of the positive electrode composite material meet the requirements of the embodiments of the present application.

[0057] In some embodiments, the angle between the magnetic field direction of the external magnetic field and the plane where the positive electrode sheet is located is 60°-90°. By making the angle between the magnetic field direction of the external magnetic field and the plane where the positive electrode sheet is located 60°-90°, the ions can be subjected to the Lorentz force in the direction perpendicular to the magnetic field, thereby promoting the migration and diffusion of the ions, which helps to accelerate the electrochemical reaction rate. When the magnetic field direction is within the above range, the external magnetic field is also likely to cause the diffusion layer at the interface of the positive electrode sheet / electrolyte to become thinner, thereby reducing the concentration polarization phenomenon, helping to maintain potential stability, and improving the efficiency of the electrochemical reaction. Under the action of the external magnetic field, the current can be more evenly distributed on the positive electrode sheet, reducing the geothermal effect and performance degradation caused by excessive local current density. The external magnetic field can also reduce the growth of dendrites by affecting the deposition mode of lithium ions, thereby improving the safety and cycle life of the battery. The external magnetic field can also affect the path of the battery electrochemical reaction and the distribution of the products. By making the magnetic field direction of the external magnetic field perpendicular to the plane where the positive electrode sheet is located, the occurrence of side reactions can be reduced, and the energy efficiency and stability of the battery can be improved.

[0058] In a second aspect, an embodiment of the present application provides an electrochemical device, including a battery and a magnetic field assembly. The battery includes a surface density of 220 g / m 2 -300g / m 2 The positive electrode sheet has a thickness greater than 400 μm and includes graphene. The magnetic field assembly is configured to generate an external magnetic field, and the external magnetic field is configured to penetrate the positive electrode sheet.

[0059] The electrochemical device provided in the embodiment of the present application includes a battery and a magnetic field assembly. The surface density of the positive electrode sheet of the battery is 220g / m 2 -300g / m 2 , the thickness of the positive electrode sheet is greater than 400μm, that is, the battery is a thick electrode battery, which improves the energy density of the battery. The positive electrode sheet includes graphene, which has extremely high conductivity and a two-dimensional planar structure, which helps to increase the transmission speed of electrons in the positive electrode sheet, reduce resistance, and thus improve the rate performance of the battery. In addition, this bed assembly can generate an external magnetic field that penetrates the positive electrode sheet, change the magnetic structure of the material in the positive electrode sheet, and construct crystals that are more conducive to the embedding and extraction of lithium ions and crystal planes that are conducive to electrochemical reactions, thereby further improving the electrochemical performance of the battery. In other words, the electrochemical device provided in the present application can simultaneously improve the energy density and rate performance of the battery, and improve the overall performance of the battery.

[0060] Among them, the external magnetic field in the electrochemical device can be provided by two magnets. By adjusting the size, spacing and relative position of the two magnets, an external magnetic field with suitable magnetic field strength and direction can be generated in the electrochemical device. The magnetic field strength can be obtained by testing with a Tesla meter.

[0061] For example, when the battery is a square battery, the magnetic field components may be disposed on two opposite sides of a large surface of the square battery, so that the external magnetic field can pass through the positive electrode sheet more.

[0062] In a third aspect, the embodiments of the present application further provide an electrical device, including the electrochemical device described above. The electrical device provided by the embodiments of the present application has all the beneficial effects of the electrochemical device described above, which will not be described in detail here.

[0063] The electrical devices provided in the embodiments of the present application include, but are not limited to, electrical equipment such as electric vehicles and energy storage systems.

[0064] The present application is further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods in the following examples that do not specify specific conditions are usually based on the conditions recommended by the manufacturer.

[0065] Example 1

[0066] (1) mixing lithium iron phosphate, Super P conductive agent, graphene and polytetrafluoroethylene in a mass ratio of 93:3:1:3 to obtain a positive electrode composite material;

[0067] (2) rolling the positive electrode composite material to obtain an electrode membrane;

[0068] (3) After laminating the electrode film and the aluminum foil, they are rolled again to obtain a positive electrode sheet, wherein the surface density of the positive electrode sheet is 250 g / m 2 ;

[0069] (4) assembling the positive electrode sheet, the negative electrode sheet and the separator to obtain a lithium ion battery; wherein the negative electrode composite material in the negative electrode sheet includes graphite, sodium carboxymethyl cellulose, conductive carbon black and styrene-butadiene rubber in a mass ratio of 96:1:1.5:1.5, and the separator adopts a commercial PP separator;

[0070] (5) An external magnetic field with a magnetic field strength of 0.75 T was applied in a direction perpendicular to the plane where the positive electrode sheet was located to conduct an electrochemical performance test.

[0071] Example 2

[0072] (1) mixing lithium iron phosphate, Super P conductive agent, graphene and polytetrafluoroethylene in a mass ratio of 93:3:1:3 to obtain a positive electrode composite material;

[0073] (2) rolling the positive electrode composite material to obtain an electrode membrane;

[0074] (3) After laminating the electrode film and the aluminum foil, they are rolled again to obtain a positive electrode sheet, wherein the surface density of the positive electrode sheet is 220 g / m 2;

[0075] (4) assembling the positive electrode sheet, the negative electrode sheet and the separator to obtain a lithium ion battery; wherein the negative electrode composite material in the negative electrode sheet includes graphite, sodium carboxymethyl cellulose, conductive carbon black and styrene-butadiene rubber in a mass ratio of 96:1:1.5:1.5, and the separator adopts a commercial PP separator;

[0076] (5) An external magnetic field with a magnetic field strength of 0.75 T was applied in a direction perpendicular to the plane where the positive electrode sheet was located to conduct an electrochemical performance test.

[0077] Example 3

[0078] (1) mixing lithium iron phosphate, Super P conductive agent, graphene and polytetrafluoroethylene in a mass ratio of 93:3:1:3 to obtain a positive electrode composite material;

[0079] (2) rolling the positive electrode composite material to obtain an electrode membrane;

[0080] (3) After laminating the electrode film and the aluminum foil, they are rolled again to obtain a positive electrode sheet, wherein the surface density of the positive electrode sheet is 300 g / m 2 ;

[0081] (4) assembling the positive electrode sheet, the negative electrode sheet and the separator to obtain a lithium ion battery; wherein the negative electrode composite material in the negative electrode sheet includes graphite, sodium carboxymethyl cellulose, conductive carbon black and styrene-butadiene rubber in a mass ratio of 96:1:1.5:1.5, and the separator adopts a commercial PP separator;

[0082] (5) An external magnetic field with a magnetic field strength of 0.75 T was applied in a direction perpendicular to the plane where the positive electrode sheet was located to conduct an electrochemical performance test.

[0083] Example 4

[0084] (1) mixing lithium iron phosphate, Super P conductive agent, graphene and polytetrafluoroethylene in a mass ratio of 93:3:1:3 to obtain a positive electrode composite material;

[0085] (2) rolling the positive electrode composite material to obtain an electrode membrane;

[0086] (3) After laminating the electrode film and the aluminum foil, they are rolled again to obtain a positive electrode sheet, wherein the surface density of the positive electrode sheet is 250 g / m 2 ;

[0087] (4) assembling the positive electrode sheet, the negative electrode sheet and the separator to obtain a lithium ion battery; wherein the negative electrode composite material in the negative electrode sheet includes graphite, sodium carboxymethyl cellulose, conductive carbon black and styrene-butadiene rubber in a mass ratio of 96:1:1.5:1.5, and the separator adopts a commercial PP separator;

[0088] (5) An external magnetic field with a magnetic field strength of 0.5 T was applied in a direction perpendicular to the plane where the positive electrode sheet was located to conduct an electrochemical performance test.

[0089] Example 5

[0090] (1) mixing lithium iron phosphate, Super P conductive agent, graphene and polytetrafluoroethylene in a mass ratio of 91:4:1.5:2.5 to obtain a positive electrode composite material;

[0091] (2) rolling the positive electrode composite material to obtain an electrode membrane;

[0092] (3) After laminating the electrode film and the aluminum foil, they are rolled again to obtain a positive electrode sheet, wherein the surface density of the positive electrode sheet is 250 g / m 2 ;

[0093] (4) assembling the positive electrode sheet, the negative electrode sheet and the separator to obtain a lithium ion battery; wherein the negative electrode composite material in the negative electrode sheet includes graphite, sodium carboxymethyl cellulose, conductive carbon black and styrene-butadiene rubber in a mass ratio of 96:1:1.5:1.5, and the separator adopts a commercial PP separator;

[0094] (5) An external magnetic field with a magnetic field strength of 0.5 T was applied in a direction perpendicular to the plane where the positive electrode sheet was located to conduct an electrochemical performance test.

[0095] Example 6

[0096] (1) mixing lithium iron phosphate, Super P conductive agent, graphene and polytetrafluoroethylene in a mass ratio of 95:2:0.5:1.5 to obtain a positive electrode composite material;

[0097] (2) rolling the positive electrode composite material to obtain an electrode membrane;

[0098] (3) After laminating the electrode film and the aluminum foil, they are rolled again to obtain a positive electrode sheet, wherein the surface density of the positive electrode sheet is 250 g / m 2 ;

[0099] (4) assembling the positive electrode sheet, the negative electrode sheet and the separator to obtain a lithium ion battery; wherein the negative electrode composite material in the negative electrode sheet includes graphite, sodium carboxymethyl cellulose, conductive carbon black and styrene-butadiene rubber in a mass ratio of 96:1:1.5:1.5, and the separator adopts a commercial PP separator;

[0100] (5) An external magnetic field with a magnetic field strength of 0.5 T was applied in a direction perpendicular to the plane where the positive electrode sheet was located to conduct an electrochemical performance test.

[0101] Example 7

[0102] (1) mixing lithium iron phosphate, Super P conductive agent, graphene and polytetrafluoroethylene in a mass ratio of 93:3:1:3 to obtain a positive electrode composite material;

[0103] (2) rolling the positive electrode composite material to obtain an electrode membrane;

[0104] (3) After laminating the electrode film and the aluminum foil, they are rolled again to obtain a positive electrode sheet, wherein the surface density of the positive electrode sheet is 250 g / m 2 ;

[0105] (4) assembling the positive electrode sheet, the negative electrode sheet and the separator to obtain a lithium ion battery; wherein the negative electrode composite material in the negative electrode sheet includes graphite, sodium carboxymethyl cellulose, conductive carbon black and styrene-butadiene rubber in a mass ratio of 96:1:1.5:1.5, and the separator adopts a commercial PP separator;

[0106] (5) An external magnetic field with a magnetic field strength of 1 T is applied in a direction perpendicular to the plane where the positive electrode sheet is located to conduct an electrochemical performance test.

[0107] Comparative Example 1

[0108] (1) mixing lithium iron phosphate, Super P conductive agent, graphene and polytetrafluoroethylene in a mass ratio of 93:3:1:3 to obtain a positive electrode composite material;

[0109] (2) rolling the positive electrode composite material to obtain an electrode membrane;

[0110] (3) After laminating the electrode film and the aluminum foil, they are rolled again to obtain a positive electrode sheet, wherein the surface density of the positive electrode sheet is 250 g / m 2 ;

[0111] (4) assembling the positive electrode sheet, the negative electrode sheet and the separator to obtain a lithium ion battery; wherein the negative electrode composite material in the negative electrode sheet includes graphite, sodium carboxymethyl cellulose, conductive carbon black and styrene-butadiene rubber in a mass ratio of 96:1:1.5:1.5, and the separator adopts a commercial PP separator;

[0112] (5) No external magnetic field is applied to the lithium-ion battery to conduct electrochemical performance testing.

[0113] Comparative Example 2

[0114] (1) mixing lithium iron phosphate, Super P conductive agent, graphene and polytetrafluoroethylene in a mass ratio of 93:3:1:3 to obtain a positive electrode composite material;

[0115] (2) rolling the positive electrode composite material to obtain an electrode membrane;

[0116] (3) After laminating the electrode film and the aluminum foil, they are rolled again to obtain a positive electrode sheet, wherein the surface density of the positive electrode sheet is 300 g / m 2 ;

[0117] (4) assembling the positive electrode sheet, the negative electrode sheet and the separator to obtain a lithium ion battery; wherein the negative electrode composite material in the negative electrode sheet includes graphite, sodium carboxymethyl cellulose, conductive carbon black and styrene-butadiene rubber in a mass ratio of 96:1:1.5:1.5, and the separator adopts a commercial PP separator;

[0118] (5) No external magnetic field is applied to the lithium-ion battery to conduct electrochemical performance testing.

[0119] Comparative Example 3

[0120] (1) mixing lithium iron phosphate, Super P conductive agent, carbon fiber (VGCF) and polytetrafluoroethylene in a mass ratio of 93:3:1:3 to obtain a positive electrode composite material;

[0121] (2) rolling the positive electrode composite material to obtain an electrode membrane;

[0122] (3) After laminating the electrode film and the aluminum foil, they are rolled again to obtain a positive electrode sheet, wherein the surface density of the positive electrode sheet is 250 g / m 2 ;

[0123] (4) assembling the positive electrode sheet, the negative electrode sheet and the separator to obtain a lithium ion battery; wherein the negative electrode composite material in the negative electrode sheet includes graphite, sodium carboxymethyl cellulose, conductive carbon black and styrene-butadiene rubber in a mass ratio of 96:1:1.5:1.5, and the separator adopts a commercial PP separator;

[0124] (5) An external magnetic field with a magnetic field strength of 0.75 T was applied in a direction perpendicular to the plane where the positive electrode sheet was located to conduct an electrochemical performance test.

[0125] Comparative Example 4

[0126] (1) mixing lithium iron phosphate, Super P conductive agent, graphene and polytetrafluoroethylene in a mass ratio of 93:3:1:3 to obtain a positive electrode composite material;

[0127] (2) rolling the positive electrode composite material to obtain an electrode membrane;

[0128] (3) After laminating the electrode film and the aluminum foil, they are rolled again to obtain a positive electrode sheet, wherein the surface density of the positive electrode sheet is 250 g / m 2 ;

[0129] (4) assembling the positive electrode sheet, the negative electrode sheet and the separator to obtain a lithium ion battery; wherein the negative electrode composite material in the negative electrode sheet includes graphite, sodium carboxymethyl cellulose, conductive carbon black and styrene-butadiene rubber in a mass ratio of 96:1:1.5:1.5, and the separator adopts a commercial PP separator;

[0130] (5) An external magnetic field with a magnetic field strength of 0.5 T was applied in a direction parallel to the plane where the positive electrode sheet was located to conduct an electrochemical performance test.

[0131] The lithium ion batteries prepared in Examples 1-7 and Comparative Examples 1-4 were subjected to electrochemical performance tests, including 2C discharge capacity and 1000 cycle capacity. The test results are shown in Table 1:

[0132] Table 1 Comparison of test results of different embodiments and comparative examples

[0133]

[0134]

[0135] From the comparison of the test results of Examples 1-7 and Comparative Examples 1-2 in Table 1, it can be found that after applying an external magnetic field to the battery, the 2C discharge specific capacity, capacity retention rate and energy density are all improved relative to when no external magnetic field is applied, indicating that the embodiment of the present application can make the battery have better electrochemical performance by applying an external magnetic field to the battery with thick electrodes. And by comparing the test results of Examples 1-3, it can be found that the higher the surface density of the positive electrode sheet, the more significant the improvement of the electrochemical performance of the battery by applying an external magnetic field. This is mainly because when the surface density of the positive electrode sheet increases, the tortuosity of the lithium ion transmission path becomes larger, and the electrical performance decreases at high rates, and the external magnetic field can optimize the transmission path of lithium ions, and the improvement of electrochemical performance is more obvious.

[0136] From the comparison of the test results of Examples 1-7 and Comparative Example 3 in Table 1, it can be found that, compared with adding carbon fiber to the positive electrode composite material, adding graphene can improve the electrochemical performance of the battery. This is mainly because graphene has extremely high conductivity and a two-dimensional planar structure, which helps to increase the transmission speed of electrons in the positive electrode sheet, reduce resistance, and thus improve the rate performance of the battery.

[0137] From the comparison of the test results of Examples 1-7 and Comparative Example 4 in Table 1, it can be found that when the magnetic field direction of the external magnetic field is perpendicular to the plane where the positive electrode sheet is located, the electrochemical performance of the battery is improved more significantly. This is mainly because the external magnetic field penetrating the positive electrode sheet can change the magnetic structure of the material in the positive electrode sheet, construct crystals that are more conducive to the insertion and extraction of lithium ions and crystal planes that are conducive to electrochemical reactions, thereby further improving the electrochemical performance of the battery.

[0138] In summary, in the embodiment of the present application, graphene is added to the positive electrode sheet, and the surface density of the positive electrode sheet is controlled at 220g / m 2 -300 g / m 2 The combination of conditions such as the intersection of the external magnetic field and the plane where the positive electrode is located enables the battery to have better electrochemical properties and produces unexpected technical effects.

[0139] The embodiments of the present application are introduced in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method of the present application and its core idea. At the same time, for technical personnel in this field, according to the idea of ​​the present application, there will be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.

Claims

1. A method for improving the electrochemical performance of a battery, characterized in that: include: placing the battery in an applied magnetic field; Wherein, the battery includes a surface density of 220g / m 2 -300g / m 2 A positive electrode sheet having a thickness greater than 400 μm; a material of the positive electrode sheet comprising graphene; and a magnetic field direction of the external magnetic field intersecting with a plane where the positive electrode sheet is located.

2. The method for improving the electrochemical performance of a battery according to claim 1, characterized in that: The magnetic field strength of the external magnetic field is 0.5T-1T.

3. The method for improving the electrochemical performance of a battery according to claim 1, characterized in that: Before placing the battery in an external magnetic field, the method further comprises: Applying a positive electrode composite material to at least one side of a current collector to form a positive electrode sheet; wherein the positive electrode composite material includes the graphene; The positive electrode sheet, the negative electrode sheet and the separator are assembled to form the battery.

4. The method for improving the electrochemical performance of a battery according to claim 3, characterized in that: The positive electrode composite material comprises a positive electrode active material, a conductive agent, the graphene and a binder; Among them, in the positive electrode composite material, the mass ratio of the positive electrode active material, the conductive agent, the graphene and the binder is (91-95):(2-4):(0.5-1.5):(2.5-3.5).

5. The method for improving the electrochemical performance of a battery according to claim 4, characterized in that: The positive electrode active material includes at least one of lithium iron phosphate and lithium manganese iron phosphate.

6. The method for improving the electrochemical performance of a battery according to claim 4, characterized in that: The conductive agent includes conductive carbon black.

7. The method for improving the electrochemical performance of a battery according to claim 4, characterized in that: The binder includes polytetrafluoroethylene.

8. The method for improving the electrochemical performance of a battery according to any one of claims 4 to 7, characterized in that: The step of applying the positive electrode composite material to at least one side of the current collector comprises: Mixing the positive electrode active material, the conductive agent, the graphene and the binder in proportion to obtain the positive electrode composite material; The positive electrode composite material is subjected to a first rolling process to obtain an electrode membrane; The electrode film is attached to at least one side of the current collector and a second rolling process is performed to obtain the positive electrode sheet.

9. The method for improving the electrochemical performance of a battery according to claim 1, characterized in that: The angle between the magnetic field direction of the external magnetic field and the plane where the positive electrode sheet is located is 60°-90°.

10. An electrochemical device, characterized in that: including a battery and a magnetic field assembly; The battery includes a surface density of 220g / m 2 -300g / m 2 A positive electrode sheet having a thickness greater than 400 μm; the positive electrode sheet comprising graphene; The magnetic field assembly is configured to generate an external magnetic field, and the external magnetic field is configured to penetrate the positive electrode sheet.

Citation Information

Patent Citations

  • Flexible-packaged high-power lithium iron phosphate power battery

    CN104577130A

  • Lithium ion battery and preparation method thereof

    CN107039651A

  • High charging rate lithium-ion battery and preparation method thereof

    CN107579245A

  • Application and method of transition metal-based positive electrode material and interface layer of magnetic field regulation and control secondary battery

    CN114361628A

  • Formation method for improving capacity of lithium battery

    CN116598622A